2008
DOI: 10.1016/j.firesaf.2007.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toxic product yields of burning cables in bench and large-scale experiments

Abstract: Toxic product yields from five commercial cables obtained from a steady state tube furnace method , the Purser furnace,) are compared with results from a large scale test, which uses the physical fire model in the proposed prEN50399-2-2 test, with the addition of effluent gas analysis, using Fourier transform infrared (FTIR), and for further comparison, a static tube furnace method (NF X 70-100). This work represents one of the first attempts to establish a relationship between bench-and large-scale toxic prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…The principle of the ISO TS 19700 tube furnace is a fixed rate feeding of the sample into a furnace under a fixed air supply (Stec et al 2008b ;Stec & Hull 2010). A good correlation between the yields for several of the major acute toxicants from fires such as CO and hydrogen cyanide (HCN) generated from large-scale tests and the steady state tube furnace has been shown (Hull et al 2008). …”
Section: Sampling and Analysis Of Isocyanates In Fire Effluentsmentioning
confidence: 99%
“…The principle of the ISO TS 19700 tube furnace is a fixed rate feeding of the sample into a furnace under a fixed air supply (Stec et al 2008b ;Stec & Hull 2010). A good correlation between the yields for several of the major acute toxicants from fires such as CO and hydrogen cyanide (HCN) generated from large-scale tests and the steady state tube furnace has been shown (Hull et al 2008). …”
Section: Sampling and Analysis Of Isocyanates In Fire Effluentsmentioning
confidence: 99%
“…Some related work has been published on the efficiency of halocarbon flame extinguishing agents CF 3 Br in methane air flames as a function of temperature [25]. This showed that the efficiency was optimised at lower temperatures, and this was attributed to longer residence times in the flame zone.…”
Section: Pa6 With Brominated Polystyrene and Antimony Trioxidementioning
confidence: 99%
“…The major factor in the assessment of fire hazard is an estimation of yields of toxic products from fires [3]. In a fire, thermal decomposition of solid material generates buoyant gaseous fuel vapours, which can burn above the solid material.…”
Section: Introductionmentioning
confidence: 99%
“…The tested cable met the Spanish NO7V-K specification, and was supplied by EuropaCable and has been described elsewhere. 15 The under-ventilated fire scenario was set up according to IEC 60695-7-50, where the furnace temperature was 825°C. Table 5 Variations of concentrations for four runs for cable Table 5 presents variations of product concentration for PVC insulated a single wire conductor for the under-ventilated fire condition.…”
Section: Repeatability Of Tube Furnacementioning
confidence: 99%